Implementasi Manajemen Keuangan Koperasi pada Pembelajaran Ekonomi Siswa Kelas XI dalam Meningkatkan Pendapatan Koperasi di MA Darul Hikmah Tulungagung (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research is motivated by the increase in cooperative income as a result of the implementation of effective financial management at MA Darul Hikmah Tulungagung. The purpose of this study is to determine the implementation of cooperative financial management in economics learning for grade XI students, the effectiveness of its implementation in increasing cooperative income, and its impact on the welfare of cooperative administrators. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation, as well as data analysis that focuses on the results of cooperative income. The research findings indicate that economics learning integrated with cooperative financial management practices can improve the effectiveness of management implementation, thus having a positive impact on increasing cooperative income. The implication of this research result is that contextual economics learning not only strengthens students' understanding of theory but also provides a real contribution to the management of school cooperatives and improving the welfare of their administrators.